A Quantitative Study on Social Media Usage Patterns and Their Effects Among Internet Users - Prasetya, Tegar Yudha; Hery, Hery; Haryani, Calandra (International Journal of Informatics and Information Systems, 2024)
This research conducts a quantitative analysis of social media usage habits and their effects among internet users, utilizing a secondary dataset of 999 respondents drawn from the Social Media Usage Survey available on Kaggle. Employing a descriptive–survey design, the study adopts a quantitative approach to examine behavioral tendencies, demographic variations, and relationships among variables such as usage duration, user motivation, privacy awareness, and intentions to reduce social media activity. Data analysis was performed using Python, incorporating descriptive statistics, crosstab analysis, and visual analytics through the Pandas, Matplotlib, and Seaborn libraries. The findings reveal that social media is deeply embedded in everyday routines, with users averaging 3.5 hours of screen time per day. Instagram, Facebook, and Twitter/X emerge as the most frequently used platforms, serving purposes that include entertainment, information access, and business promotion. Video-based content dominates user preferences, reflecting the broader global media consumption trend. Additionally, 69% of respondents acknowledge that social media influences their purchasing behavior, while 65% express moderate to high levels of privacy concern. Notably, about 68% of users report an intention to reduce their screen time, indicating a growing awareness of the need for digital balance. Correlation analysis shows that individuals with longer screen durations and heightened privacy concerns are more likely to intend reducing their usage, suggesting that excessive engagement may drive self-regulatory behavior. These insights illustrate the dual nature of social media—as a medium for empowerment and connectivity, yet simultaneously a potential source of psychological fatigue. Overall, this study contributes empirical evidence supporting efforts to foster healthy and responsible digital engagement, enriching the broader discourse on digital well-being, online literacy, and sustainable technology use in the modern digital landscape.